Farming a New Economically viable Fish Species: Kisinja (Barbus altianalis) - Aruho, C.; Ondhoro, C.C. (Aquaculture Research and Development Center, National Fisheries Resources Research Institute, 2010)
Kisinja (Barbus altianalis)is an indigenous omnivorous fish, of high economic value in Uganda. It was widely distributed in most lakes and rivers in the country but its stocks were depleted due to overfishing and degradation of its natural habitat. 1t can grow up to a maximum length of 120m and a weight of 15kg in the wild and grows faster, attains larger size than commonly farmed fishes in Uganda, including the Nile tilapia, the African catfish, and mirror carp. Kisinja is a highly valuable table fish with good taste and aroma especially when smoked. Increased production of Kisinja is therefore necessary to meet economic and nutritional benefits of the communities and conservation of the spedes.
Keywords: Farming; fish species